Performance Measurement of Management Study-Program Based on Balanced Scorecard from Student's Perception - Ardansyah ARDANSYAH; Ayu Ichda Mardatila (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Performance measurement is a method or instrument used to record and assess any achievement of anaction based on goals, objectives, and strategies, so progress of an organization could be known and itsaccountability and quality of decision-making could be improved. In contrast, executives are likely toignore non-financial performance, such as customers’ satisfaction, process of productivity and costeffectivenessused to produce goods and services, and employees’ empowerment and commitment inproviding the goods and services for consumers’ satisfaction. Problem of this research is how thePerformance of Management Study Program in Bandar Lampung University based on balanced scorecardfrom students’ perception is. Therefore, this study aims to investigate the performance perceived bystudents derived from balanced scorecard. The research used literature study. Its outcome showed that theperformance of the Management Study Program in 2013 perspective, in general, is pretty good.